دور المؤسسّة الماليزية للتنمية الإسلامية في الرقابة على منتجات الأغذية والتجميل الحلال: دراسة حالة وصفية : The Role of the Malaysian Islamic Development Corporation in Monitoring Halal Food and Cosmetic Products: A Descriptive Analysis Case - Mahmoud Mohamed Ali Mahmoud Edris (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2021)
ملخص تهدف هذه الدراسة إلى إبراز الدّور الإرشادي، والتوجيهي، والمعنوي الذي تقدّمه المؤسسّة الماليزية للتنمية الإسلامية في جميع جوانب الحياة الماليزية بوصفه أسلوبًا كاملاً وشاملاً يدعو إليه الإسلام كقانون يستقي من الشريعة أحكامه، وقد أشارت قاعدته الذهبية إلى بيان المتشابهات من المحرمات مصداقًا لقوله صلى الله عليه وسلم: "إنّ الحلال بيّن وإن الحرام بيّن وبينهما أمور مشتبهات لا يعلمهن كثير من الناس"إلخ. وكذا قانون التغذية الخاص بالمؤسسّة الماليزية الذي يعتمد على استهلاك لحوم الحيوانات التي أحلّ الله أكلها، والانتفاع بجلدها كطيبات سخرها الله. كما تبيّن الدراسة اهتمام المؤسسّة بمتابعة معاملة المجتمع غير المسلم للحيوانات باحترام وعناية حيث تدعو المؤسسّة لممارسة الذبح المنصوص عليه في الإسلام دون الصعق للحيوان أو رميه بطريقة غير إنسانية. وللتطبيق على أرض الواقع تناشد المؤسّسة الجهات الرقابية بمتابعة تطبيق المواصفات القياسية الخاصة بمنتجات الحلال، وإن مؤسّسة التنمية الماليزية تركّز على المكوّنات الحلال للأغذية ومستحضرات التجميل والأدوية وغيرها مما هو مُفيد، مستصحبةً في ذلك المعايير الأخلاقية. وقد اعتمد الباحث على المنهج الوصفي، والمنهج التحليلي الاستنباطي بُغية الوصول إلى الفائدة المرجُوّة. وتضمّ الدراسة محورين: المحور الأول: يتناول دور المؤسسّة الماليزية للتنمية في الرقابة على صادرات وواردات منتجات الأغذية والأدوية الماليزية. المحور الثاني: يتضمن وضعية شعار علامة (الحلال) في المنتجات الماليزية بين المتاجرة الربحية الدولية، والرقابة الشرعية المهنية التي تمارسها المؤسّسة. Abstract This study aims to highlight the guiding, and moral role that the Malaysian Foundation for Islamic Development presents in all aspects of Malaysian life as a complete and comprehensive method advocated by Islam as a law that draws from the Sharia and its provisions based on the prophetic saying: “The permissible is clear, and the forbidden is clear, and there are suspicious matters between them that many people are not aware of…”. It also shows that Malaysian Foundation for Halal food act rely on consuming Halal meet only, with permissibility to benefit from slaughtered animals’ skin as pure material which was given to us by Allah. The study also shows the Foundation’s interest in following up the non-Muslim community’s treatment of animals, and that they should treat them with respect and care. The Foundation advocates to perform slaughtering animals as stipulated in Shariah, avoiding electric-shock of animals, or throwing them in an inhuman manner. In order to make this goal a reality on the ground, the Foundation appeals to the regulatory authorities to follow up the implementation of the standard specifications for halal products. The Malaysian foundation focuses on halal food ingredients, cosmetics products, medicines, and other Halal related products that are useful to the mankind, accompanied by ethical standards. The researcher relied on the descriptive and deductive analytical method, with the aim to reach the desired outcomes. The study includes two axes: First, it deals with the role of the Malaysian Development Foundation in supervising exports and imports of Malaysian food and medicine products. Second: it studies the situation of the (Halal) brand logo on Malaysian products assessing its profitability in international trade arena and Shariah supervisory professionalism which is adhered to by the Foundation